Reduction of high-grade spondylolisthesis using minimally invasive spine surgery-transforaminal lumbar interbody fusion “trial-” technique: a technical note with case series - Mukesh Kumar; Vikramaditya Rai; Amit Joshi; Shrish Nalin; Manoj Kumar Gandhi (Asian Spine Journal, 2024)
This retrospective case series evaluated the effectiveness of minimally invasive spine surgery-transforaminal lumbar interbody fusion (MIS-TLIF) using the “trial-in-situ” technique for reducing high-grade spondylolisthesis. The surgical management of grade ≥III spondylolisthesis has been controversial, with various methods documented in the literature, including in-situ fusion, in-situ trans-sacral delta fixation, distraction techniques, and external reduction techniques. Recently, MIS techniques have gained popularity. This study analyzed 18 cases of high-grade spondylolisthesis treated with MIS-TLIF using the “trial-in-situ” technique. The clinical outcomes were assessed using the Visual Analog Scale (VAS) and the modified Oswestry Disability Index (mODI) scores. The spinopelvic parameters and sagittal balance were also analyzed. Preoperatively, the spinopelvic parameters were deranged, with a mean pelvic tilt of 28.31°, which improved to 13.91° postoperatively. Similarly, the sacral slope improved from 45.65° to 38.01°. VAS and mODI scores improved postoperatively, indicating the effectiveness of the “trial-in-situ” technique in reducing high-grade spondylolisthesis and achieving a better sagittal profile and spinopelvic parameters. The findings indicate that MIS-TLIF using the “trial-in-situ” technique is a viable and effective method for treating high-grade spondylolisthesis.